NILAI PENDIDIKAN KARAKTER DALAM CERITA RAKYAT KABUPATEN BANTUL KI AGENG MANGIR (KAJIAN FOLKLOR) - Himawan, Riswanda Riswan (MIMESIS, 2020)
The problem in this study is how the structure of the folklore "Ki Ageng Mangir", the function of folklore from Bantul district "Ki Ageng Mangir", as well as any moral values contained in the folklore. This study aims to describe the structure, function and the moral value of the folklore "Ki Ageng Mangir" The research method used is descriptive, data collection techniques using reading and note-taking techniques, the data generated in this study are written data.The results of the study indicate that the Ki Ageng Mangir people's stories have a function as the source of reference for historical events in Bantul district, the values contained in this story are cultural, religious and moral values.